A meta-analysis of deltoid ligament on ankle joint fracture combining deltoid ligament injury - Yang, XiaoLing; Zeng, Jianshuang; Yang, Wei; Dela Rosa, Ronnell D; Jiang, Zhixia (Frontiers in Surgery, 2023)
Purpose: Ankle fracture combined with deltoid ligament(DL) injury results in decreased stability of ankle mortise, reduced contact surface between tibial and talus, increased local stress, and increased postoperative complications. The purpose of this meta-analysis was to evaluate the postoperative effects of repairing ligaments in ankle fractures with DL rupture. Methods: According to the steps of the Cochrane systematic review, the related literatures from PubMed, Embase and the Cochrane Library Databases were retrieved as of September 1, 2021, and all relevant randomized controlled trials and retrospective studies were collected. The evaluation indicators include medial clear space(MCS), visual analogue scale(VAS), American Orthopedic Foot and Ankle Society(AOFAS), complications rate. Meta-analysis was conducted by RevMan® 5.3 provided by the Cochrane collaboration. Results: A total of 388 patients (195 patients in the ligament repair group and 193 patients in the non-repair group) were included in 7 clinical trials. Meta-analysis data showed there were no statistically significant differences between the ligament repair group and non-repair group in final follow-up VAS, final AOFAS and postoperative MCS (P=0.50, P=0.04, P= 0.14, P= 0.14, respectively). Final follow-up MCS and complications rate in ligament repair group were smaller than those in the non-repair group and were statistically significant (P < 0.00001, P=0.006, respectively). Conclusion: Although there was no difference in in final follow-up VAS, final follow-up AOFAS and postoperative MCS between experimental group and control group, It's statistically significant in final follow-up MCS and complications rate. Ligament repair could reduce the width of MCS, restore ankle stability, reduce the incidence of complications and lead to a better prognosis.